CD-ROM based JomJaring courseware / Ummu Aiman Al-Abidah Zainal Abidin - Zainal Abidin, Ummu Aiman Al-Abidah (2012)
Sport is a compulsory and valued part of the school's curriculum and is an integral part of a child's development. In Malaysian schools, netball is commonly played by female students in school as early as Year 4 or 10 years old students. To give the student a fun learning experience, JomJaring Courseware is developed. JomJaring Courseware is a learning tool based on interactive multimedia that could helps users to learn netball in a simpler, easier and more interesting form compared to traditional method of learning. JomJaring also includes an interactive quiz to test user’s understanding about rules of netball. The courseware enables users to study in a flexible way based on their choice of time, place and learning pace. JomJaring is based on the chapter three of ‘Modul Latihan Sukan’ for Primary School provided by Sport Unit, Ministry Of Education Of Malaysia and covers the basic understanding of netball games. This courseware was developed based on ADDIE Model where it consists of Analysis, Design, Development, Implementation and Evaluation. During analysis, the learning problem, the goals and objectives, the audience’s needs, existing knowledge and any other relevant characteristics are identified through reading references. The second stage is design phase where storyboard and sitemap are developed. The development phase concerns about using software such as Adobe Photoshop, Adobe Professional Flash, and Window Live Movie Maker Software in creating, designing and implementing the five elements of multimedia. Testing and bugs are detection in implementation phase and are corrected before evaluation is made through the testing by targeted users which are primary school students along with distribution of questionnaire. Result shows that JomJaring has the potential to be expanded throughout the country by all primary schools to create a brighter future for potential players.